A Mild, Facile, One-Pot Synthesis of Zinc Azido Porphyrins as Substrates for Use in Click Chemistry - Bryden, Francesca; Boyle, Ross W. (Synlett, 2013)
The conversion of porphyrins bearing primary amines into zinc-protected azido porphyrins utilising a diazo-transfer reagent is reported. This method allows the mild, facile, and one-pot synthesis of zinc azido porphyrins bearing a range of meso functionalities, producing the required porphyrin in high yield. Reactivity of the azide functionality is demonstrated by subsequent model click reactions to produce triazole derivatives.
Keywords: porphyrins; azides; zinc; click chemistry; diazotransfer reagent